Modafinil improves attentional performance in healthy, non-sleep deprived humans at doses not inducing hyperarousal across species. (October 2017) - Cope, Zackary A.; Minassian, Arpi; Kreitner, Dustin; MacQueen, David A.; Milienne-Petiot, Morgane; Geyer, Mark A.; Perry, William; Young, Jared W.
Abstract: The wake-promoting drug modafinil is frequently used off-label to improve cognition in psychiatric and academic populations alike. The domain-specific attentional benefits of modafinil have yet to be quantified objectively in healthy human volunteers using tasks validated for comparison across species. Further, given that modafinil is a low-affinity inhibitor for the dopamine and norepinephrine transporters (DAT/NET respectively) it is unclear if any effects are attributable to a non-specific increase in arousal, a feature of many catecholamine reuptake inhibitors (e.g., cocaine, amphetamine). These experiments were designed to test for domain-specific enhancement of attention and cognitive control by modafinil (200 and 400 mg) in healthy volunteers using the 5-choice continuous performance task (5C-CPT) and Wisconsin Card Sort Task (WCST). An additional cross-species assessment of arousal and hyperactivity was performed in this group and in mice (3.2, 10, or 32 mg/kg) using species-specific versions of the behavioral pattern monitor (BPM). Modafinil significantly enhanced attention (d prime) in humans performing the 5C-CPT at doses that did not affect WCST performance or induce hyperactivity in the BPM. In mice, only the highest dose elicited increased activity in the BPM. These results indicate that modafinil produces domain-specific enhancement of attention in humans not driven by hyperarousal, unlike other drugs in this class, and higher equivalent doses were required for hyperarousal in mice. Further, these data support the utility of using the 5C-CPT across species to more precisely determine the mechanism(s) underlying the pro-cognitive effects of modafinil and potentially other pharmacological treatments. Highlights: Modafinil improved attention in healthy, non-sleep deprived volunteers. Attention is improved at doses that do not induce hyperarousal, indicating domain specificity. Modafinil doses producing hyperarousal in mice may not reflect therapeutic doses in humans.